Africa: The management education challenge - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2017)
The research evidence for this second volume of Africa: The Management Education Challenge is based primarily on around 40 in-depth, face-to-face, semi-structured interviews lasting about two to three hours. The interviewees were drawn from academia, business, media and government with expertise in management education.